Effect of grape bunch sunlight exposure and UV radiation on phenolics and volatile composition of Vitis vinifera L. cv. Pinot noir wine. (15th April 2015) - Song, Jianqiang; Smart, Richard; Wang, Hua; Dambergs, Bob; Sparrow, Angela; Qian, Michael C.
Highlights: Sunlight and UV exposure increased anthocyanins, total pigment, total phenolics and tannin content in wine. Sunlight exposure and UV resulted in increase of nerol, geraniol and citronellol but not linalool in the wine. Neither sunlight nor UV treatment showed any impact on the concentration of β-damascenone. Abstract: The effect of canopy leaf removal and ultraviolet (UV) on Pinot noir grape and wine composition was investigated in this study. Limited basal leaf removal in the fruit zone was conducted, compared to shaded bunches. The UV exposure was controlled using polycarbonate screens to block UV radiation, and acrylic screens to pass the UV. The results showed that bunch sunlight and UV exposure significantly increased the Brix and pH in the grape juice, and increased substantially wine colour density, anthocyanins, total pigment, total phenolics and tannin content. Bunch sunlight and UV exposure affected terpene alcohols, C13 -norisprenoids and other volatile composition of the wine differently. Sunlight exposure and UV resulted in increase of nerol, geraniol and citronellol but not linalool. Sunlight exposure slightly increased the concentration of β-ionone, but the increase was not statistically significant for UV treatment. Neither sunlight nor UV treatment showed any impact on the concentration of β-damascenone.